C-H functionalization of indoles by 3d transition-metal catalysis - Jagtap, Rahul A.; Punji, Benudhar (Asian Journal of Organic Chemistry, 2019)
Over the past decade, the use of 3d transition metal for the regioselective C-H bond functionalization of indoles has significantly increased. Particularly, advances in manganese, iron, cobalt, nickel and copper catalysis have demonstrated the selective C(2)-H and C(3)-H arylation, alkenylation, alkynylation and alkylation to a greater extent. Similarly, the C-O and C-N bond-forming reactions are manifested via direct C-H bond activation by these earth-abundant metals. The emergence of 3d metals in selective functionalization of the biologically relevant indoles and related heteroarenes would make this protocol more attractive for practical applications. Herein, we provide a brief overview of 3d transition metal-catalyzed (mostly Mn, Fe, Co, Ni and Cu) C-H functionalization of indoles and related heteroarenes.
Keywords: 3d transition metal; C-H functionalization; Indole; indoline